Paham Allah Dalam Pengalaman Para Nelayan di Ambon: Suatu Diskursus Teologi Kontekstual - Brian Lory Lorwens (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2021)
The fishermen are constantly faced with various challenges when working. In the challenges they face, they believe a supreme power will guide them in their work. The work experience of fishers with different challenges becomes a medium to build an understanding of God. This study aims to see how fishers understand God based on work experience. This study uses qualitative research methods with in-depth interview techniques, observation, and literature study. After collecting the data, the next step is to analyze the data based on the practical model. The study results found that the fishermen experienced God through storms, waves, and bad weather. The experience becomes a way to share and interpreting God in their lives. The catch of the fishermen also gives an understanding of God, who gives blessings to their lives. Through this reality, the fishermen rely on God to provide them with blessings, join in the work, and answer their prayers. God is the Source of Hope, and this is an attempt to contextualize theology based on the work experience of the fishermen. Putting hope in God is a form of faith in God's promises and inclusion.